2002
DOI: 10.1634/stemcells.20-6-522
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of Size‐Sieved Stem Cells into Electrically Active Neural Cells

Abstract: Size-sieved stem (SS) cells isolated from human bone marrow and propagated in vitro are a population of cells with consistent marker typing, and can form bone, fat, and cartilage. In this experiment, we demonstrated that SS cells could be induced to differentiate into neural cells under experimental cell culture conditions. Five hours after exposure to antioxidant agents (β-mercaptoethanol ± retinoic acid) in serum-free conditions, SS cells expressed the protein for nestin, neuron-specific enolase (NSE), neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(109 citation statements)
references
References 32 publications
6
102
0
1
Order By: Relevance
“…We have previously investigated the signaling pathways involved in chondrogenesis under the control of type I and type II collagen, TGF␤1, and platelet-rich plasma (3,4,32,33,38). Building on the observations from our previous studies, we established a coculture system in which MSCs were directed toward chondrogenesis under the influence of mature chondrocytes, thereby creating a better simulation of physiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously investigated the signaling pathways involved in chondrogenesis under the control of type I and type II collagen, TGF␤1, and platelet-rich plasma (3,4,32,33,38). Building on the observations from our previous studies, we established a coculture system in which MSCs were directed toward chondrogenesis under the influence of mature chondrocytes, thereby creating a better simulation of physiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously investigated the methods of purification, characterization, differentiation, and application of multipotent MSCs (10,(32)(33)(34)(35). We have also studied the expression of matrix proteins, the type I and type II collagens, which induce chondrogenesis in human MSCs under the influence of TGF␤1 (3).…”
mentioning
confidence: 99%
“…hMSCs can be induced to differentiate into multiple lineages, including bone, fat, cartilage, as well as neuron in vitro (1,(3)(4)(5). Transplanted MSCs are able to differentiate into neuronal lineage and improve the functions of central nervous system (CNS) with ischemia (6), Parkinson disease (7), Alzheimer disease (8), spinal cord injury (9, 10), and other neurodegenerative disorders (11, 12) modeled in rodents.…”
Section: Human Mesenchymal Stem Cells (Hmscs)mentioning
confidence: 99%
“…However, the density of the voltage-gated sodium channels is very low compared to mature neurons, suggesting that the undifferentiated hMeSCs are incapable of producing action potentials. Attempts to induce action potentials in hMeSCs using depolarizing current pulses have confirmed that undifferentiated MeSCs isolated from the adult BM of humans or rodents do not generate action potentials [14,21,25,[37][38][39][40].…”
Section: Membrane Properties Of Neuron-like Cells Differentiated Frommentioning
confidence: 99%
“…Previous calcium imaging studies have show that cells differentiated from adult MeSCs, adult NSCs, and embryonic stem cells respond to depolarization with KCl or the application of the neurotransmitter l-glutamate with an increase in cytoplasmic Ca 2þ levels [27,31,38,55,56]. These transient changes in the Ca 2þ levels are important for regulating neuronal differentiation, transmitter selection, and axonal targeting in immature neurons [57,58].…”
Section: Development Of Kcl and L-glutamate-induced Increases In Cytomentioning
confidence: 99%